Comparison of the effects of butorphanol–midazolam–medetomidine and butorphanol–azaperone–medetomidine in wild common palm civets (Paradoxurus musangus) - Ahmad, Ali Anwar; Douay, Guillaume; Low, Mary Ruth; Fabbri, Suria; Chen, Hui Cheng (Elsevier, 2021)
Objective: To assess the efficacy of butorphanol–azaperone–medetomidine (BAM) and butorphanol–midazolam–medetomidine (BMM) protocols for immobilization of wild common palm civets (Paradoxurus musangus) with subsequent antagonization with atipamezole. Study design: Prospective, randomized, blinded clinical trial. Animals: A total of 40 adult wild common palm civets, 24 female and 16 male, weighing 1.5–3.4 kg. Methods: The civets were randomly assigned for anesthesia with butorphanol, azaperone and medetomidine (0.6, 0.6 and 0.2 mg kg–1, respectively; group BAM) or with butorphanol, midazolam and medetomidine (0.3, 0.4 and 0.1 mg kg–1, respectively; group BMM) intramuscularly (IM) in a squeeze cage. When adequately relaxed, the trachea was intubated for oxygen administration. Physiological variables were recorded every 5 minutes after intubation. Following morphometric measurements, sampling, microchipping and parasite treatment, medetomidine was reversed with atipamezole at 1.0 or 0.5 mg kg–1 IM to groups BAM and BMM, respectively. Physiological variables and times to reach the different stages of anesthesia were compared between groups. Results: Onset time of sedation and recumbency was similar in both groups; time to achieve complete relaxation and tracheal intubation was longer in group BAM. Supplementation with isoflurane was required to enable intubation in five civets in group BAM and one civet in group BMM. All civets in group BAM required topical lidocaine to facilitate intubation. End-tidal carbon dioxide partial pressure was lower in group BAM, but heart rate, respiratory rate, rectal temperature, peripheral hemoglobin oxygen saturation and mean arterial blood pressure were not different. All civets in both groups recovered well following administration of atipamezole. Conclusions and clinical relevance: Both BAM and BMM combinations were effective for immobilizing wild common palm civets. The BMM combination had the advantage of producing complete relaxation that allowed intubation more rapidly.